Effect of Binder Concentration on Density and Combustion Performance of Sawdust Biopellets - Siti Fauziah; Sarinah Pakpahan; Aswin Aswin; Vivi Dia Afrianti S (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Sawdust is an abundant by-product of the wood processing industry and has significant potential as a raw material for biopellet production. However, the quality and combustion performance of biopellets are strongly influenced by the binder concentration used during the production process. This study investigates the effect of binder concentration on the density and combustion performance of sawdust-based biopellets. Biopellets were prepared with binder concentrations of 35%, 40%, and 45% and evaluated through density measurement, bomb calorimeter testing, and combustion analysis. The results show that increasing binder concentration enhances density from 1.16 to 1.26 g/cm³, indicating improved structural compactness. However, the higher heating value (HHV) decreases from 14.44 ± 0.13 MJ/kg to 12.23 ± 0.13 MJ/kg due to dilution of energy-rich biomass. Combustion analysis reveals increased ignition time and longer burning duration at higher binder content, indicating more stable but less reactive combustion. These findings demonstrate a trade-off between mechanical strength and energy performance. Therefore, a binder concentration of 35% is recommended for energy-efficient applications, while higher concentrations may be suitable for durability-oriented uses.